2020
DOI: 10.1186/s41118-020-00088-1
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behavioural differences and risk-taking differences among born-abroad and native university students in Italy

Abstract: There is a substantial lack of information in the literature on affective and sexual behaviours in youths with migratory backgrounds, despite immigrants' immediate descendants growing in recent years in many destination countries. In order to fill this gap, we use original information, collected by the "Sexual and Emotional Life of Youths (SELFY)" survey carried out in Italy in 2017. We aim to provide a deeper understanding of sexual behaviours by comparing, for the very first time, university students with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…These responses were dichotomized into: 'Both parents born in Sweden' (reference category), and ' At least one parent born abroad' . Studies have associated Swedish-born and foreign backgrounds with diverse sexual attitudes and behaviors, as well as differences in socioeconomic and community factors [39,40].…”
Section: Background Variablesmentioning
confidence: 99%
“…These responses were dichotomized into: 'Both parents born in Sweden' (reference category), and ' At least one parent born abroad' . Studies have associated Swedish-born and foreign backgrounds with diverse sexual attitudes and behaviors, as well as differences in socioeconomic and community factors [39,40].…”
Section: Background Variablesmentioning
confidence: 99%
“…A systematic comparison between the affective and sexual behaviours of Italian native students and those with a migratory background was offered by Gabrielli, Paterno, and Strozza (2020). Their results showed that male students not born in Italy have a greater inclination for liberal attitudes towards sex than their native counterparts, while there are no notable differences between foreign-born and native women.…”
mentioning
confidence: 99%